Process Optimization for the Detection of Listeria monocytogenes and Listeriolysin O from Spiked Chicken Meat by Polymerase Chain Reaction - Swetha, C.S.; Rao, T. Madhava; Babu, A. Jagadeesh; Kumar, E. (Journal of Meat Science, 2014)
The study was undertaken to standardize PCR assay for detection of L. monocytogenes and Listeriolysin O from livestock foods and compare its efficacy with conventional cultural methods. A set of primer derived from iap gene and hly A gene were used for detection of L. monocytogenes and Listeriolysin O in the PCR assay. Electrophoresis analysis revealed the specific amplification products at 131 bp and 456 bp respectively for iap and hlyA. Among the three different template preparation methods viz. genomic DNA extraction, heat lysis and lysis buffer methods, heat lysis method was simple, rapid and reliable. The specificity of the standardized PCR assay was tested by subjecting 8 isolates including L. monocytogenes and seven other non-Listeria monocytogenes bacteria. Only L. monocytogenes isolates gave specific product of 131 bp for iap and 456 bp for hlyA genes respectively. The sensitivity of the PCR assay was evaluated by subjecting serial 10-fold dilution of pure culture of L. monocytogenes from 4.0X107 cfu /ml to 4.0 cfu /ml to PCR assay. The minimum detection level was found to be 4 cfu/ml. Four different broths were evaluated to assess their PCR compatibility. Two non-selective broths (BHI and TSB) produced bands in all four treatments, but they were found as light. Among selective broths, LEB gave very bright bands to treatment-1 and 2 and bright bands to other treatments whereas PALCAM medium gave bright bands to treatment-1 and 2, and light bands to other two treatments. In spiking studies the minimum detection level for L.monocytogenes and Listeriolysin O was 4.0 cfu by PCR in LEB broth incubated for 24 hrs. LEB broth gave better results than PALCAM when incubated for 18 and 24hr.
Keywords: Listeria monocytogenes; Listeriolysin O; Spiked studies in chicken; PCR